'Stories Are Like Genes': A Tribute to A.S. Byatt (1936-2023) - Lara-Rallo, Carmen (AEDEAN, 2024)
This article explores A.S. Byatt’s life and work (1936-2023), as a tribute to the writer after her death in November 2023. It departs from Byatt’s view of stories as genes (since “they keep part of us alive after the end of our story”), and aims to prove how this applies to the author herself in terms of the timeless quality of her production. In order to do so, the article offers a panoramic survey of Byatt’s oeuvre, including her novels, short stories, and critical texts. Although the structural principle of this exploration is chronological, following a bio-bibliographical perspective, the tribute flows from text to text by analysing recurrent themes, images, character types, and spaces. In this way, the article discovers fruitful connections between Byatt’s works in the broad context of her writing career. All this is supported by an extensive and updated bibliography of primary and secondary sources.
La editora de AEDEAN Nexus 2024.01 me ha autorizado a incluir esta publicación en el Repositorio de la UMA en formato de acceso abierto (correo electrónico de 28/03/2025).
Keywords: Byatt, A. S 1936-2023 - Crítica e interpretación; A.S. Byatt; Tribute; Novels; Criticism; Short stories; Life and work